Construction method of polyhydric alcohol functionalized hollow covalent organic framework and boron removal application of polyhydric alcohol functionalized hollow covalent organic framework
Through the template method and the functionalization method of precise control, a polyol functionalized hollow COFs adsorbent was prepared, which solved the problem of functionalization difficulties and poor structural stability of the existing COFs-based boron removal adsorbents, and achieved efficient boron removal performance and good cycle stability.
Patent Information
- Application Number
- CN202411714013.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing COFs-based boron removal adsorbents have difficulty in functionalization, poor structural stability and low adsorption capacity, which limit their effect on boron removal in aqueous solution.
The COFs layer was grown on the surface of the silicon medium by the template method, and the polyol functional groups were anchored through the precise control of chemical substances such as N,N-dimethylformamide and megamine chloride, and the reconstruction and functionalization of the COFs structure were realized, and the polyol functional hollow COFs adsorbent was finally prepared.
The functionalization and structural optimization of COFs adsorbents are achieved, and the boron removal performance in aqueous solution is improved, and boron can be quickly enriched, and the good adsorption performance remains maintained after five cycles.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of adsorption separation functional materials, and relates to a method for constructing a polyol functionalized hollow covalent organic framework and its boron removal application. Background Art
[0002] Boron and its compounds, due to their unique chemical stability and electronic properties, play a key role in semiconductor materials, high-performance composite materials, special glass and drug synthesis. They are widely used in many fields such as building materials, metallurgy, agriculture, medicine, nuclear industry, etc., and are an important cornerstone to support global scientific and technological progress and industrial upgrading. Although boron is an essential trace element in organisms, the adaptability of animals, plants and humans to boron in water is very limited. Excessive boron intake can cause a series of health problems including physiological metabolic disorders, nervous system damage and functional damage to liver and kidney organs. In recent years, with the rapid development of the boron industry, the discharge of boron-containing wastewater has increased year by year, which has seriously disrupted the boron cycle in the natural environment, posed a threat to the ecosystem, and further affected the human living environment. The continuous improvement of environmental protection requirements is an important trend and key measure to protect the human living environment and social sustainable development. This puts forward more stringent requirements for the rational development of liquid boron resources and the deep treatment technology of boron-containing wastewater in the boron industry. Therefore, establishing a new green and efficient boron removal method with independent intellectual property rights and achieving harmless treatment of boron-containing wastewater is of great significance to maintaining the stability of the boron cycle in water bodies in the natural environment. It is highly consistent with the guiding spirit of strengthening the control of new pollutants in the "Action Plan for the Control of New Pollutants" and is an active response to the needs of the national green development strategy.
[0003] At present, the technologies for removing boron from aqueous solutions include extraction, acid precipitation, multi-stage crystallization and adsorption. Among them, the adsorption method has shown broad application potential in the field of separation technology with its advantages of simple operation, economic and environmental protection, and renewability, and has received widespread attention. Covalent organic framework (COFs) materials, with their excellent characteristics such as ultra-large specific surface area, adjustable pore size and densely distributed modifiable sites, have shown broad application prospects in the field of adsorption separation and have attracted much attention and favor from the industry. However, as a member of emerging materials, COFs materials still face shortcomings such as functional difficulties, poor structural stability and difficulty in clarifying structure-activity relationships, which limit their performance and application value. Therefore, the innovative development of new COFs material preparation technology that integrates functionalization, highly ordered structure and stable properties is a key way to promote the application of COFs materials in the field of adsorption separation.
[0004] The ordered structure of COFs-based adsorbents, the loading amount of monomers in the pores, and the morphology, these factors together affect the interaction efficiency between COFs adsorbents and target molecules, and determine their adsorption performance. By precisely designing the reaction conditions of the functionalization process and regulating the reversibility of covalent bonds, the release and recombination of COFs basic units can be achieved. When the basic units are released into the solution, the accessibility of the sites available for modification is greatly enhanced. In this process, the functionalization of COFs adsorbents can be achieved. Subsequently, the functionalized COFs basic units are restacked due to the conjugated forces between the units, and the covalent bonds are formed again, achieving structural optimization at the microscopic level.
[0005] Hollow-structured micro-nano materials are widely used in the development of micro-nano adsorbent materials due to their unique advantages such as light weight, strong site accessibility and good dispersibility. The introduction of hollow structure is an effective way to regulate the structure-activity relationship of adsorbent materials and improve the accessibility between target and functional sites. COFs material growth was successfully introduced on the template surface through a solid template-assisted surface polymerization strategy, and hollow COFs adsorbents were obtained by subsequently removing the template. Although the strong conjugated interaction between COF units promotes their assembly, there are still challenges in the precise control of synthesis, especially the difficulty in accurately regulating the stacking mode of units. Therefore, most products are dominated by non-ideal AB stacking patterns, which significantly hinders the formation of regular channels inside COFs materials, thereby weakening their structural characteristics and expected functional performance, and limiting the potential of COFs materials in high-performance applications. Therefore, the performance of COFs adsorbents can be effectively improved by exploring the structure-activity relationship between the growth process of COFs layers and the design of post-functionalization reaction conditions during its preparation through the template method, achieving a high degree of structural order and a high loading amount of monomers, and then stabilizing and modifying and constructing hollow structures. Summary of the invention
[0006] In order to solve the problems of COFs-based boron removal adsorbents in the prior art, such as difficulty in functionalization, poor structural stability and low adsorption capacity, the present invention proposes a method for constructing a polyol-functionalized hollow covalent organic framework (HSPCOF) for rapid boron removal in aqueous solution.
[0007] The present invention first grows a COFs layer on the surface of a silicon medium by a template method, then uses N,N-dimethylformamide (DMF) as a solvent and meglumine chloride (Cl-NMDG) as a functional monomer, and through precise control of the reaction conditions, anchors the polyol functional group on the basic unit of COFs, and reconstructs the COFs structure during the functionalization process, and then realizes the preparation of a polyol functionalized hollow COFs adsorbent after stabilization modification and removal of the template. Through precise control of the reaction temperature and solvent of the functionalization process, a series of HSPCOF boron removal adsorbents with different monomer loadings and structural optimization degrees are obtained, and a series of studies are conducted on their boron adsorption performance.
[0008] In order to achieve the above technical purpose, the technical solution adopted by the present invention is:
[0009] (1) Preparation of pre-aldehyde functionalized silica nanosphere template (SiO2-CHO NST)
[0010] First, a mixed solution A of anhydrous ethanol, deionized water and ammonia water is prepared. Under stirring conditions, tetraethyl orthosilicate (TEOS) is added to the mixed solution A in small amounts and multiple times for the first reaction, centrifuged, washed with anhydrous ethanol for several times and then dispersed, then an ethanol solution of 3-aminopropyltriethoxysilane (APTES) is added, stirred for the second reaction, centrifuged, washed with anhydrous ethanol for several times, dispersed with methanol, acetic acid and terephthalaldehyde are added, stirred for the third reaction, centrifuged, washed with ethanol for several times, and the obtained solid is SiO2-CHO NST, which is vacuum dried for standby use;
[0011] (2) Preparation of covalent organic framework (BCOF)
[0012] The SiO2-CHO NST prepared in step (1) is placed in a round-bottom flask, and then methanol and acetic acid are added. After ultrasonic dispersion, the mixture is placed in a water bath and stirred. A methanol solution of 1,4-dialdehyde-2,5-divinylbenzene (DVA) and a methanol solution of 1,3,5-tri(4-aminophenyl)benzene (TAPB) are added through a syringe at regular intervals. After the reaction is completed, the mixture is centrifuged and washed with methanol and anhydrous ethanol for several times to remove residual reagents. The obtained solid BCOF is vacuum dried for later use;
[0013] (3) Preparation of polyol functionalized adsorbent (PCOF)
[0014] 1) Epichlorohydrin and meglumine are dispersed in DMF, stirred for reaction, and the mixture is extracted with acetone and filtered to obtain a pure white mixture, which is then vacuum dried to completely remove acetone, and finally Cl-NMDG is obtained as a viscous transparent liquid;
[0015] 2) The BCOF prepared in step (2) is placed in a round-bottom flask and dispersed with DMF, and then Cl-NMDG is added. After ultrasonic dispersion, nitrogen is introduced for deoxygenation under stirring, and copper chloride dihydrate, pentamethyldiethylenetriamine (PMEDTA) and ascorbic acid (AA) are added in sequence. The reaction is sealed and completed. After cooling to room temperature, the mixture is centrifuged and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid PCOF is vacuum dried for use.
[0016] (4) Preparation of polyol-functionalized hollow covalent organic frameworks (HSPCOFs)
[0017] 1) The product PCOF obtained in step (3) and terephthalic acid are dispersed in methanol at low temperature, sodium borohydride is slowly added under stirring, and the reaction time is t1, and then the temperature is slowly increased and placed in an oil bath to continue the reaction time t2, and the mixture is naturally cooled to room temperature and separated by centrifugation, and washed with deionized water and ethanol several times to remove residual reagents, and the obtained solid SPCOF is vacuum dried for use;
[0018] 2) Add SPCOF to a sodium hydroxide solution, stir for reaction, centrifuge, and wash with deionized water and ethanol several times to remove residual reagents. The obtained solid HSPCOF is vacuum dried for later use.
[0019] Preferably, in step (1), in the mixed solution A, the volume ratio of anhydrous ethanol, deionized water and ammonia water is 15-45 mL: 2.5-7.5 mL: 1-3 mL;
[0020] The dosage ratio of the mixed solution A, TEOS, APTES ethanol solution, acetic acid and terephthalaldehyde is 18-60mL: 2-6.5mL: 2-10mL: 0.1-0.3mL: 0.1-0.6g; wherein, TEOS is added twice, 5% of the total amount of TEOS is added for the first time, and 95% of the total amount of TEOS is added for the second time after an interval of 0.5-1h; the concentration of the APTES ethanol solution is 2.5% (v / v);
[0021] The reaction temperature is 25-35°C, the stirring speed is 200-400rpm; the first reaction time is 8-12h; the second reaction time is 8-12h; the third reaction time is 3-6h;
[0022] Preferably, in step (2), the usage ratio of SiO2-CHO NST, methanol, acetic acid, methanol solution of DVA, and methanol solution of TAPB is 50-150 mg: 25-75 mL: 0.1-0.3 mL: 5-15 mL: 5-15 mL, wherein the concentration of the methanol solution of DVA is 4.4 g / L, and the concentration of the methanol solution of TAPB is 5.6 g / L.
[0023] The reaction temperature in the water bath is 25-35°C, the stirring speed is 200-400rpm, the interval between monomer additions is 15-20min, the amount added each time is 0.2-0.6mL, and the reaction time after the addition is completed is 24-48h.
[0024] Preferably, in step (3) 1), the ratio of epichlorohydrin to meglumine is 4.15-12.45 mL:9.55-28.65 g, the stirring reaction temperature is 45-55° C., and the stirring reaction time is 20-26 h.
[0025] Preferably, in step (3) 2), the amount ratio of BCOF, Cl-NMDG, cupric chloride dihydrate, PMEDTA and AA is 50-150 mg: 0.2-0.6 g: 50-150 mg: 0.1-0.3 mL: 25-75 mg, the stirring speed is 200-300 rpm, the sealing reaction temperature is 45-50 ° C, and the reaction time is 20-26 h.
[0026] Preferably, in step (4) 1), the amount ratio of PCOF, terephthalic acid and sodium borohydride is 50-150 mg: 0.12-0.36 g: 1-3 g, the rotation speed is 200 rpm, the low temperature is 0 to -18 ° C, the initial reaction time t1 is 100-120 min, then the temperature is raised to an oil bath temperature of 30-35 ° C, and the reaction time t2 is continued for 20-26 h.
[0027] Preferably, in step (4) 2), the concentration of the sodium hydroxide solution is 2M, the stirring speed is 200-400 rpm, the stirring reaction temperature is 30-35° C., the stirring reaction time is 6-8 h, and the centrifugal speed is 4000-6000 rpm.
[0028] The polyol functionalized hollow covalent organic framework prepared by the present invention is used for boron removal in aqueous solution. Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:
[0029] The present invention is based on the template method and the reversible regulation of covalent bonds, and prepares a hollow polyol functionalized covalent organic framework and applies it to the removal of boron in aqueous solution. ① The hollow structure of HSPCOF improves the accessibility of adsorption sites, which can achieve rapid enrichment of boron, reaching 87.94% of the maximum adsorption amount within 180 minutes, and adsorption equilibrium within 5 hours; ② A simple reaction process is required to achieve the functionalization and structural optimization of COFs materials, simplifying the reaction steps for obtaining high-performance COFs materials; ③ After five cycles, HSPCOF still has good adsorption performance and can achieve boron enrichment. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the preparation process of the polyol functionalized hollow covalent organic framework (HSPCOF) of the present invention.
[0031] Figure 2 SEM and TEM images of materials at various stages in Example 1.
[0032] Figure 3 These are infrared spectra of the product BCOF in (2) in Example 1, the product PCOF at different reaction temperatures, and the product SPCOF.
[0033] Figure 4 This is the infrared spectrum of the monomer Cl-NMDG in (1) of (3) in Example 1.
[0034] Figure 5 1 is the XRD spectrum of the product PCOF at different reaction temperatures in Example 4.
[0035] Figure 6 1 is an elemental analysis data diagram of the product PCOF at different reaction temperatures in Example 4.
[0036] Figure 7 The pH results and Zeta potential analysis of Example 5 are shown.
[0037] Figure 8 The adsorption kinetics experimental results of Example 6 are shown.
[0038] Fig. 9 The equilibrium adsorption experiment results of Example 7 are shown.
[0039] Fig.10 The results of the regeneration performance experiment of HSPCOF in Example 8 are shown. DETAILED DESCRIPTION
[0040] Figure 1 Schematic diagram of the preparation process of polyol-functionalized hollow covalent organic framework (HSPCOF).
[0041] Embodiment 1:
[0042] (1) Preparation of pre-aldehyde functionalized silica nanosphere template (SiO2-CHO NST)
[0043] Mix 15mL of anhydrous ethanol, 2.5mL of deionized water and 1mL of ammonia water in a 50mL single-mouth round-bottom flask, then add 0.1mL of TEOS, stir at 200rpm for 0.5h, and then add 2mL of TEOS to react for a certain time. Collect by centrifugation, wash with anhydrous ethanol several times to remove residual reagents, disperse with 15mL of anhydrous ethanol in a 50mL single-mouth round-bottom flask, add 2mL of 2.5% vol APTES ethanol solution, and stir at 200rpm for 8h. After centrifugation, wash with anhydrous ethanol several times to remove residual reagents, add 25mL of methanol to a 50mL single-mouth round-bottom flask to disperse it, add 0.1mL of acetic acid and 0.1g of terephthalaldehyde, and stir at 200rpm for 8h. After centrifugation, wash with ethanol several times to remove residual reagents, and the resulting solid is SiO2-CHO NST, which is placed in a vacuum oven to dry for use.
[0044] (2) Preparation of covalent organic framework (BCOF)
[0045] 50 mg of SiO2-CHO NST prepared in step (1) was placed in a 50 mL round-bottom flask, and then 25 mL of methanol and 0.1 mL of acetic acid were added. After ultrasonic dispersion, it was placed in a water bath at 35°C and stirred at 200 rpm. Every 15 minutes, 0.2 mL of DVA methanol solution (22 mg of DVA dissolved in 5 mL of methanol) and 0.2 mL of TAPB methanol solution (28 mg of TAPB dissolved in 5 mL of methanol) were added through a syringe. After all the monomers were added, the reaction was maintained for 48 hours, centrifuged, and washed several times with methanol and anhydrous ethanol to remove residual reagents. The obtained solid (BCOF) was placed in a vacuum oven to dry for use.
[0046] (3) Preparation of polyol functionalized adsorbent (PCOF)
[0047] Preparation of Cl-NMDG: 4.15 mL of epichlorohydrin and 9.55 g of meglumine were dispersed in DMF and stirred at 45 °C for 20 h. The mixture was extracted with acetone and filtered to obtain a pure white mixture. The mixture was transferred to a vacuum dryer and vacuum dried to completely remove acetone, and Cl-NMDG was finally obtained as a viscous transparent liquid for use in the next step.
[0048] 50 mg of the BCOF prepared in step (2) was placed in a 50 mL round-bottom flask, and then 20 mL of DMF and 0.2 g of Cl-NMDG were added. After ultrasonic dispersion, the mixture was stirred at 200 rpm at 50 ° C. Nitrogen was introduced for 0.5 h to remove oxygen in the reaction system as much as possible. 50 mg of copper chloride dihydrate, 0.1 mL of PMEDTA and 25 mg of AA were added in sequence. The mixture was sealed and reacted for 24 h. After cooling to room temperature, it was centrifuged and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (PCOF) was placed in a vacuum oven to dry for later use.
[0049] (4) Preparation of polyol-functionalized hollow covalent organic frameworks (HSPCOFs)
[0050] 1) 50 mg of the product PCOF obtained in step (3) and 0.12 g of terephthalic acid were dispersed in 20 mL of methanol in a 50 mL round-bottom flask at zero degrees, stirred at 200 rpm, and then 1 g of sodium borohydride was slowly added. After reacting for 2 hours, the temperature was slowly raised to room temperature, transferred to an oil bath at 35°C and reacted for 24 hours, naturally cooled to room temperature, separated by centrifugation, and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (SPCOF) was placed in a vacuum oven to dry for use.
[0051] 2) 50 mg of the product SPCOF obtained in step 1) was placed in a 50 mL round-bottom flask, 20 mL of 2 M sodium hydroxide solution was added, and etching was performed at 200 rpm for 6 h. After centrifugation at 5000 rpm, the residual reagents were removed by washing with deionized water and ethanol several times, and the obtained solid (HSPCOF) was placed in a vacuum oven to dry for later use.
[0052] Figure 2 The SEM and TEM images of the materials at each stage in Example 1 are respectively the SEM (ad) and TEM (eh) images of BCOF, PCOF, SPCOP, and HSPCOF, from which the morphology and structure of the materials can be clearly seen. The COF layers a and e of BCOF show a large thickness due to the disorder of their stacking form. After functionalization and structural optimization, it can be seen in b and f that the particle size of PCOF is slightly smaller and the thickness is reduced, which is due to the transformation of the stacking form. Through stabilization modification, there is no significant change in its overall structure. After etching the template, the hollow structure of HSPCOF can be clearly observed in d and h.
[0053] Figure 3 The infrared spectra of the product BCOF in (2) of Example 1, the product PCOF at different reaction temperatures in (3), and the product SPCOF in (4) of 1) are shown in Figure 1. The chlorine is at 735 cm -1The absorption peak at 3370 cm indicates that the Cl-NMDG monomer reacts with the vinyl group in the channel to anchor the polyol on the inner wall of the channel. -1 A clear hydroxyl absorption peak was observed at 1100 cm -1 The disappearance of the silica absorption peak at 40° indicates the complete removal of the silica template.
[0054] Figure 4 The infrared spectrum of the monomer Cl-NMDG in (1) of (3) in Example 1 shows that the chlorine in the Cl-NMDG monomer (735 cm -1 ) corresponds to the epoxy part (910 cm -1 ) and the absence of the hydroxyl group in meglumine (3370 cm -1 ), which shows the successful synthesis of Cl-NMDG.
[0055] Embodiment 2:
[0056] (1) Preparation of pre-aldehyde functionalized silica nanosphere template (SiO2-CHO NST)
[0057] Mix 30mL of anhydrous ethanol, 5mL of deionized water and 2mL of ammonia water in a 100mL single-mouth round-bottom flask, then add 0.2mL of TEOS, stir at 200rpm for 0.5h, and then add 4mL of TEOS to react for a certain time. Collect by centrifugation, wash with anhydrous ethanol several times to remove residual reagents, disperse with 20mL of anhydrous ethanol in a 50mL single-mouth round-bottom flask, add 3mL of 2.5% vol APTES ethanol solution, and stir at 200rpm for 8h. After centrifugation, wash with anhydrous ethanol several times to remove residual reagents, add 25mL of methanol to a 50mL single-mouth round-bottom flask to disperse it, add 0.1mL of acetic acid and 0.2g of terephthalaldehyde, and stir at 200rpm for 8h. After centrifugation, wash with ethanol several times to remove residual reagents, and the resulting solid is SiO2-CHO NST, which is placed in a vacuum oven and dried for use.
[0058] (2) Preparation of covalent organic framework (BCOF)
[0059] 100 mg of SiO2-CHO NST prepared in step (1) was placed in a 100 mL round-bottom flask, and then 50 mL of methanol and 0.1 mL of acetic acid were added. After ultrasonic dispersion, it was placed in a water bath at 35°C and stirred at 200 rpm. Every 15 minutes, 0.4 mL of DVA methanol solution (44 mg of DVA dissolved in 10 mL of methanol) and 0.4 mL of TAPB methanol solution (56 mg of TAPB dissolved in 10 mL of methanol) were added through a syringe. After all the monomers were added, the reaction was maintained for 48 hours, centrifuged, and washed several times with methanol and anhydrous ethanol to remove residual reagents. The obtained solid (BCOF) was placed in a vacuum oven to dry for use.
[0060] (3) Preparation of polyol functionalized adsorbent (PCOF)
[0061] Preparation of Cl-NMDG: 8.3 mL of epichlorohydrin and 19.1 g of meglumine were dispersed in DMF and stirred at 50 °C for 24 h. The mixture was extracted with acetone and filtered to obtain a pure white mixture. The mixture was transferred to a vacuum dryer and vacuum dried to completely remove acetone, and Cl-NMDG was finally obtained as a viscous transparent liquid for use in the next step.
[0062] 100 mg of the BCOF prepared in step (2) was placed in a 100 mL round-bottom flask, and then 40 mL of DMF and 0.4 g of Cl-NMDG were added. After ultrasonic dispersion, the mixture was stirred at 200 rpm at 50 ° C. Nitrogen was introduced for 0.5 h to remove oxygen in the reaction system as much as possible. 100 mg of copper chloride dihydrate, 0.2 mL of PMEDTA and 50 mg of AA were added in sequence. The mixture was sealed and reacted for 24 h. After cooling to room temperature, it was centrifuged and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (PCOF) was placed in a vacuum oven to dry for later use.
[0063] (4) Preparation of polyol-functionalized hollow covalent organic frameworks (HSPCOFs)
[0064] 1) 100 mg of the product PCOF obtained in step (3) and 0.24 g of terephthalic acid were dispersed in 30 mL of methanol in a 50 mL round-bottom flask at zero degrees, stirred at 200 rpm, and then 2 g of sodium borohydride was slowly added. After reacting for 2 hours, the temperature was slowly raised to room temperature, transferred to an oil bath at 35°C and reacted for 24 hours, naturally cooled to room temperature, separated by centrifugation, and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (SPCOF) was placed in a vacuum oven to dry for use.
[0065] 2) 100 mg of the product SPCOF obtained in step 1) was placed in a 50 mL round-bottom flask, 20 mL of 2 M sodium hydroxide solution was added, and the mixture was etched at 200 rpm for 6 h. After centrifugation at 5000 rpm, the mixture was washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (HSPCOF) was placed in a vacuum oven and dried for later use.
[0066] Embodiment 3:
[0067] (1) Preparation of pre-aldehyde functionalized silica nanosphere template (SiO2-CHO NST)
[0068] Mix 45mL of anhydrous ethanol, 7.5mL of deionized water and 3mL of ammonia water in a 100mL single-mouth round-bottom flask, then add 0.3mL of TEOS, stir at 200rpm for 0.5h, and then add 6mL of TEOS to react for a certain time. Collect by centrifugation, wash with anhydrous ethanol several times to remove residual reagents, disperse with 60mL of anhydrous ethanol in a 100mL single-mouth round-bottom flask, add 10mL of 2.5% vol APTES ethanol solution, and stir at 200rpm for 8h. After centrifugation, wash with anhydrous ethanol several times to remove residual reagents, add 25mL of methanol to a 50mL single-mouth round-bottom flask to disperse it, add 0.3mL of acetic acid and 0.6g of terephthalaldehyde, and stir at 200rpm for 8h. After centrifugation, wash with ethanol several times to remove residual reagents, and the resulting solid is SiO2-CHO NST, which is placed in a vacuum oven to dry for use.
[0069] (2) Preparation of covalent organic framework (BCOF)
[0070] 75 mg of SiO2-CHO NST prepared in step (1) was placed in a 100 mL round-bottom flask, and then 50 mL of methanol and 0.1 mL of acetic acid were added. After ultrasonic dispersion, it was placed in a water bath at 35°C and stirred at 200 rpm. Every 15 minutes, 0.3 mL of DVA methanol solution (33 mg of DVA dissolved in 7 mL of methanol) and 0.3 mL of TAPB methanol solution (42 mg of TAPB dissolved in 7 mL of methanol) were added through a syringe. After all the monomers were added, the reaction was maintained for 48 hours, centrifuged, and washed several times with methanol and anhydrous ethanol to remove residual reagents. The obtained solid (BCOF) was placed in a vacuum oven to dry for use.
[0071] (3) Preparation of polyol functionalized adsorbent (PCOF)
[0072] Preparation of Cl-NMDG: 12.45 mL of epichlorohydrin and 28.65 g of meglumine were dispersed in DMF and stirred at 55 °C for 26 h. The mixture was extracted with acetone and filtered to obtain a pure white mixture. The mixture was transferred to a vacuum dryer and vacuum dried to completely remove acetone, and Cl-NMDG was finally obtained as a viscous transparent liquid for use in the next step.
[0073] 100 mg of the BCOF prepared in step (2) was placed in a 100 mL round-bottom flask, and then 40 mL of DMF and 0.4 g of Cl-NMDG were added. After ultrasonic dispersion, the mixture was stirred at 300 rpm at 50 ° C. Nitrogen was introduced for 0.5 h to remove oxygen in the reaction system as much as possible. 100 mg of copper chloride dihydrate, 0.2 mL of PMEDTA and 50 mg of AA were added in sequence. The mixture was sealed and reacted for 24 h. After cooling to room temperature, it was centrifuged and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (PCOF) was placed in a vacuum oven to dry for later use.
[0074] (4) Preparation of polyol-functionalized hollow covalent organic frameworks (HSPCOFs)
[0075] 1) 150 mg of the product PCOF obtained in step (3) and 0.36 g of terephthalic acid were dispersed in 30 mL of methanol in a 50 mL round-bottom flask at zero degrees, stirred at 200 rpm, and then 3 g of sodium borohydride was slowly added. After reacting for 2 hours, the temperature was slowly raised to room temperature, transferred to an oil bath at 35° C. and reacted for 24 hours, naturally cooled to room temperature, separated by centrifugation, and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (SPCOF) was placed in a vacuum oven to dry for use.
[0076] 2) 150 mg of the product SPCOF obtained in step 1) was placed in a 50 mL round-bottom flask, 30 mL of 2 M sodium hydroxide solution was added, and the mixture was etched at 200 rpm for 6 h. After centrifugation at 5000 rpm, the mixture was washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (HSPCOF) was placed in a vacuum oven and dried for later use.
[0077] Example 4: Effect of reaction temperature on adsorbent structure and functional monomer loading
[0078] 50 mg of BCOF prepared in step (2) of Experimental Example 1 was placed in a 100 mL round-bottom flask, and then 20 mL of DMF and 0.2 g of Cl-NMDG were added. After ultrasonic dispersion, the mixture was stirred at 300 rpm at different temperatures (30, 40, 45, 50, 55, 60 ° C). Nitrogen was introduced for 0.5 h to remove oxygen in the reaction system as much as possible. 100 mg of copper chloride dihydrate, 0.2 mL of PMEDTA and 50 mg of AA were added in sequence. The mixture was sealed and reacted for 24 h. After cooling to room temperature, it was centrifuged and washed several times with deionized water and ethanol to remove residual reagents. The obtained solid (PCOF) was placed in a vacuum oven and dried.
[0079] Figure 5 The XRD spectra of the product PCOF at different reaction temperatures in Example 4 are shown. From the XRD analysis, it can be seen that at 318K to 323K, the four peaks at 2.84°, 4.85°, 5.65° and 7.37° become more obvious, and the peak moves from 2.59° to 2.84° and enhances, showing an AA stacking pattern. The enhancement of the peaks shows that functionalization at the optimal reaction temperature can effectively improve the crystal form of the product.
[0080] Figure 6 It is an elemental analysis data diagram of the product PCOF at different reaction temperatures in Example 4. After the Cl-NMDG monomer is grafted and modified, the nitrogen-carbon ratio will change accordingly. The grafting amount is positively correlated with the nitrogen-carbon ratio. The increase in the nitrogen-carbon ratio shows that functionalization at the optimal reaction temperature can effectively increase the monomer modification amount of the product.
[0081] Example 5: Effect of Solution pH on Boron Adsorption
[0082] Accurately weigh 6 portions of 5 mg of HSPCOF prepared under the conditions described in Example 1, add them into 5 mL of boron solution with a pH value of 5, 6, 7, 8, 9, 10 and a concentration of 200 mg / L, respectively, place at 25°C for 24 hours, and then centrifuge. After the solution is collected and passed through a membrane, the concentration of remaining boron in the solution is detected by azomethine-H acid spectrophotometry. Three parallel experiments are performed.
[0083] Figure 7 The pH results and Zeta potential analysis of Example 5 show that the adsorption of HSPCOF is the largest in an environment with a pH of 9, reaching 114.86 mg g -1 , and this process is less affected by electrostatic effects.
[0084] Example 6: Effect of adsorption time on boron adsorption
[0085] Accurately weigh 8 portions of 5 mg of HSPCOF prepared under the conditions described in Example 1, add them into 5 mL of a boron solution with a concentration of 200 mg / L and a pH value of 9, place them at 25°C, keep them for 5, 15, 30, 60, 120, 180, 240, 300, and 360 minutes, then centrifuge and collect the solution, pass it through a membrane, and detect the concentration of residual boron by azomethine-H acid spectrophotometry. Three parallel experiments were performed.
[0086] Figure 8 The adsorption kinetics experimental results of Example 6 show that HSPCOF can achieve rapid enrichment of boron, reaching 87.94% of the maximum adsorption amount within 180 minutes and reaching adsorption equilibrium within 5 hours.
[0087] Example 7: Effect of initial boron concentration on adsorption
[0088] Accurately weigh 6 portions of 5 mg of HSPCOF prepared under the conditions described in Example 1, add them into 5 mL of boron solution (pH = 9) with concentrations of 100, 200, 300, 500, 700, 1000 mg / L, respectively, place at 25°C, keep for 24 hours, and collect the adsorbed liquid by centrifugation; 35°C and 45°C, the same operation as above at 25°C. After passing through the membrane, the concentration of residual boron is detected by azomethine-H acid photometry, and three parallel experiments are performed.
[0089] Fig. 9 The equilibrium adsorption experiment results of Example 7 show that as the initial concentration of boric acid increases, the adsorption capacity of HSPCOF gradually increases and can reach 162.01 mg g -1 , and the fitting results of the adsorption data are more consistent with the Langmuir model, indicating that the material belongs to uniform single molecular layer adsorption.
[0090] Example 8: Effect of adsorbent regeneration on boron adsorption
[0091] Accurately weigh 5 mg of HSPCOF prepared under the conditions described in Example 1, add 5 mL of a boron solution with a concentration of 200 mg / L and a pH value of 9, keep it at 25°C for 24 hours, then centrifuge it, remove the solution, wash it with deionized water, add 10 mL of 0.1 mol / L hydrochloric acid as an eluent, continue to stand for 24 hours, centrifuge it, remove the solution, wash it with deionized water until it is neutral, this is one cycle, and a total of five cycles are performed. After the adsorption liquid and the desorption liquid pass through the membrane, the concentration of the remaining boron is detected by the azomethine-H acid spectrophotometry, and three groups of parallel experiments are performed.
[0092] Fig.10The results of the regeneration performance experiment of HSPCOF in Example 8 show that after 5 cycles, HSPCOF still has relatively stable adsorption performance and good regeneration performance.
Claims
1. A method for constructing a polyol functionalized hollow covalent organic framework, characterized in that: The steps include: (1) Preparation of pre-aldehyde functionalized silica nanosphere template SiO2-CHO NST First, a mixed solution A of anhydrous ethanol, deionized water and ammonia water is prepared. Under stirring conditions, tetraethyl orthosilicate TEOS is added to the mixed solution A in small amounts and multiple times for the first reaction, centrifuged, washed with anhydrous ethanol for several times and then dispersed, then an ethanol solution of 3-aminopropyltriethoxysilane APTES is added, stirred for the second reaction, centrifuged, washed with anhydrous ethanol for several times, dispersed with methanol, acetic acid and terephthalaldehyde are added, stirred for the third reaction, centrifuged, washed with ethanol for several times, and the obtained solid is SiO2-CHO NST, which is vacuum dried for standby use; (2) Preparation of covalent organic framework layer BCOF The SiO2-CHO NST prepared in step (1) is placed in a round-bottom flask, and then methanol and acetic acid are added. After ultrasonic dispersion, the mixture is placed in a water bath and stirred. A methanol solution of 1,4-dialdehyde-2,5-divinylbenzene DVA and a methanol solution of 1,3,5-tris(4-aminophenyl)benzene TAPB are added through a syringe at regular intervals. After the reaction is completed, the mixture is centrifuged and washed with methanol and anhydrous ethanol for several times to remove residual reagents. The obtained solid BCOF is vacuum dried for later use; (3) Preparation of polyol functionalized adsorbent PCOF 1) Epichlorohydrin and meglumine are dispersed in DMF, stirred for reaction, and the mixture is extracted with acetone and filtered to obtain a pure white mixture, which is then vacuum dried to completely remove acetone, and finally Cl-NMDG is obtained as a viscous transparent liquid; 2) placing the BCOF prepared in step (2) in a round-bottom flask and dispersing it with DMF, then adding Cl-NMDG, and after ultrasonic dispersion, introducing nitrogen to deoxygenate under stirring, and sequentially adding cupric chloride dihydrate, pentamethyldiethylenetriamine PMEDTA and ascorbic acid AA, sealing the flask until the reaction is complete, cooling to room temperature and centrifuging, and washing with deionized water and ethanol several times to remove residual reagents, and the obtained solid PCOF is vacuum dried for use; (4) Preparation of polyol-functionalized hollow covalent organic framework HSPCOF 1) The product PCOF obtained in step (3) and terephthalic acid are dispersed in methanol at low temperature, sodium borohydride is slowly added under stirring, and the reaction time is t1, and then the temperature is slowly increased and placed in an oil bath to continue the reaction time t2, and the mixture is naturally cooled to room temperature and separated by centrifugation, and washed with deionized water and ethanol several times to remove residual reagents, and the obtained solid SPCOF is vacuum dried for use; 2) Add SPCOF to a sodium hydroxide solution, stir for reaction, centrifuge, and wash with deionized water and ethanol several times to remove residual reagents. The obtained solid HSPCOF is vacuum dried for later use.
2. The construction method according to claim 1, characterized in that: In step (1), In the mixed solution A, the volume ratio of anhydrous ethanol, deionized water and ammonia water is 15-45 mL: 2.5-7.5 mL: 1-3 mL; The dosage ratio of the mixed solution A, TEOS, APTES ethanol solution, acetic acid and terephthalaldehyde is 18-60mL: 2-6.5mL: 2-10mL: 0.1-0.3mL: 0.1-0.6g; wherein, TEOS is added twice, 5% of the total amount of TEOS is added for the first time, and 95% of the total amount of TEOS is added for the second time after an interval of 0.5-1h; the concentration of the APTES ethanol solution is 2.5% (v / v); The reaction temperature is 25-35°C, the stirring speed is 200-400rpm; the first reaction time is 8-12h; the second reaction time is 8-12h; and the third reaction time is 3-6h.
3. The construction method according to claim 1, characterized in that: In step (2), the usage ratio of SiO2-CHO NST, methanol, acetic acid, methanol solution of DVA, and methanol solution of TAPB is 50-150 mg: 25-75 mL: 0.1-0.3 mL: 5-15 mL: 5-15 mL, wherein the concentration of the methanol solution of DVA is 4.4 g / L, and the concentration of the methanol solution of TAPB is 5.6 g / L.
4. The construction method according to claim 1, characterized in that: In step (2), the reaction temperature in the water bath is 25-35° C., the stirring speed is 200-400 rpm, the monomer addition interval is 15-20 min, the amount added each time is 0.2-0.6 mL, and the reaction time after the addition is completed is 24-48 h.
5. The construction method according to claim 1, characterized in that: In step (3) 1), the ratio of epichlorohydrin to meglumine is 4.15-12.45 mL:9.55-28.65 g, the stirring reaction temperature is 45-55° C., and the stirring reaction time is 20-26 h.
6. The construction method according to claim 1, characterized in that: In step (3) 2), the dosage ratio of BCOF, Cl-NMDG, cupric chloride dihydrate, PMEDTA and AA is 50-150 mg: 0.2-0.6 g: 50-150 mg: 0.1-0.3 mL: 25-75 mg.
7. The construction method according to claim 1, characterized in that: In step (3) 2), the stirring speed is 200-300 rpm, the temperature of the sealed reaction is 45-50° C., and the reaction time is 20-26 h.
8. The construction method according to claim 1, characterized in that: In step (4) 1), the amount ratio of PCOF, terephthalic acid and sodium borohydride is 50-150 mg: 0.12-0.36 g: 1-3 g, the rotation speed is 200 rpm, the low temperature is 0 to -18 ° C, the initial reaction time t1 is 100-120 min, then the temperature is raised to an oil bath temperature of 30-35 ° C, and the reaction time t2 is continued for 20-26 h.
9. The construction method according to claim 1, characterized in that: In step (4) 2), the concentration of the sodium hydroxide solution is 2M, the stirring speed is 200-400 rpm, the stirring reaction temperature is 30-35° C., the stirring reaction time is 6-8 h, and the centrifugal speed is 4000-6000 rpm.
10. The polyol functionalized hollow covalent organic framework prepared by the construction method according to any one of claims 1 to 9 is used for boron removal in aqueous solution.
Citation Information
Patent Citations
Preparation method and application of rapid high-selectivity gold extraction adsorbent of bionic magnetotactic bacteria
CN115193416A
Hollow porous high-activity boron affinity imprinted polymer adsorbent as well as preparation method and application thereof
CN115368510A
Hollow nano covalent organic framework and preparation method thereof
CN116041642A
Boric acid functionalized covalent organic framework microcapsule adsorbent as well as preparation method and application thereof
CN116786089A
Ultralight and compressible covalent organic framework aerogel, preparation method and application of ultralight and compressible covalent organic framework aerogel
CN117753382A